ANALISIS KEBUTUHAN: PEMBELAJARAN BERBASIS WEB PADA MAHASISWA VOKASIONAL - Ina Yulianti; Ida Hamidah; Mumu Komaro; Ahmad Mudzakir (Jurnal Teknologi Informasi dan Pendidikan, 2020)
Entering the digital era, communication and information technology continues to experience development. Therefore the development of these technologies must be adopted and utilized for educational purposes. The availability of teaching materials in the sample environment under study is still very limited, existing learning resources are still general in nature and still contain concepts with conventional formats. The purpose of this study was to determine the need for website-based learning for vocational students. The research sample was taken using Purposive Sampling as many as five Chemical Engineering students. Data collection is done by semi-structured interview methods, unstructured observation and field documentation to determine the urgency of the need for web-based teaching materials. The research instrument was the researcher herself with the help of interview guides. The collected data is then analyzed using Miles and Huberman's analysis theory, then triangulated to find out its validity. Based on the triangulation results from the three data, students are very interested in web-based learning. This research is expected to provide recommendations to policy makers to be able to meet the needs of web-based teaching materials for vocational students to improve their learning outcomes.